Pembuatan Website Pelayanan Pemerintahan Desa Sukalaba: Meningkatkan Kualitas Pelayanan Dan Keterbukaan Informasi Bagi Masyarakat - Reihan Mutaqin; Abdul Bahits; Ana Regitha Dwi Saputri; Muhamad Nur Fauzan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The internet has been a highly influential phenomenon in recent times, impacting technological advancements and various fields of knowledge. Internet development also directly affects the growth of websites. Initially, websites were not very popular due to limited services. However, they are now widely used and offer various services, such as news portals, email providers, and social media platforms. The use of computerized systems becomes more convenient when integrated with information systems based on websites, offering a user-friendly interface for data input and accuracy. In the current internet era, websites are essential for both government and private institutions, providing information to the public without constraints of distance and time. The Sukalaba Village Government Office, located in the Gunungsari subdistrict, is a government institution that serves the community. However, it faces challenges in its services, primarily related to the lack of easy access for the public to obtain information. This research aims to systematically and structurally develop the Sukalaba Village Government Service website. The process involves needs analysis, planning, content development, website design, implementation and testing, training, and launching. Through this approach, it is expected that the website will enhance service quality and increase transparency of information for the community. The website is expected to be an effective platform for the public to access essential information about their village and participate in its development. The creation of the Sukalaba Village Government Service website has successfully improved service quality and information availability for the community. The interactive and responsive design ensures easy access to information through various devices. With the website's launch, the community now enjoys fast and convenient access to relevant village-related information, encouraging greater transparency and community participation in the development process. In conclusion, the development of the Sukalaba Village Government Service website has significantly improved service quality and information transparency for the community, benefiting both the village government and its residents.